Christian America? what evangelicals really want - Smith, Christian 1960- (Univ. of California Press, 2000)
In recent decades Protestant evangelicalism has become a conspicuous and--to many Americans--worrisome part of this country's cultural and political landscape. But just how unified is the supposed constituency of the Christian Coalition? And who exactly are the people the Christian Right claims to represent? In the most extensive study of American evangelicals ever conducted, Christian Smith explores the beliefs, values, commitments, and goals of the ordinary men and women who make up this often misunderstood religious group. Based on data from a three-year national study, including more than 200 in-depth interviews, Christian America? assesses the common stereotype of evangelicals as intolerant, right-wing, religious zealots seeking to impose a Christian moral order through political force. What Smith finds instead are people vastly more diverse and ambivalent than this stereotype suggests-- the labels "conservative" and "liberal" are too simplistic for understanding their approaches to public life and political action.--From publisher description.
Keywords: Geschichte 1900-2000; Christianisme et culture - États-Unis - Histoire - 20e siècle; Christianisme et politique - États-Unis - Histoire - 20e siècle; Evangelischen; Kerk en maatschappij; Évangélisme - États-Unis - Histoire - 20e siècle; Geschichte; Christianity and culture -- United States -- History -- 20th century; Christianity and politics -- United States -- History -- 20th century; Evangelicalism -- United States -- History -- 20th century; Christentum; Fundamentalismus; Evangelikale Bewegung; USA